Hypoxia Imaging and Biological Evaluation of the Radiosensitizing Effect of Oleanolic Acid. (28th August 2018) - Wang, Hui; Zhang, Yu; Yu, Wenjing; Xue, Yangyang; Xiao, Liang; Xu, Huiqin
Abstract : Background and Purpose . The aim of this study was to evaluate the radiosensitizing effect of oleanolic acid (OA) on C6 rat glioma and the changes in tumor biology during radiosensitization therapy on 18 F-fluoromisonidazole ( 18 F-FMISO) positron emission tomography/computed tomography (PET/CT). Methods . The radiosensitizing effect of OA on C6 tumors was assessed in vivo by measuring the tumor inhibitory rate and rat survival time. Meanwhile, rats with C6 tumors were imaged with 18 F-FMISO PET/CT during radiosensitization therapy. Tumor-to-muscle ratio (TMR) of 18 F-FMISO maximum uptake was calculated by region of interest analysis. Changes in tumor biology after therapy were assessed with immunohistochemical staining. 18 F-FMISO uptake was analyzed in relation to expression of tumor biomarkers including hypoxia-inducible factor (HIF)-1 α, glucose transporter (Glut-1), the proliferation antigen Ki67, tumor suppressor P53, and microvessel density (MVD). Results . The results showed that OA combined with radiation inhibited the growth rates of tumors and prolonged the survival period of tumor-bearing rats effectively ( χ 2 = 12.5, p < 0.01). 18 F-FMISO PET/CT indicated decreases in hypoxia after radiosensitization therapy. Statistical differences were observed in TMR of the irradiation group and OA combined with irradiation group ( t = 3.32, p < 0.05). HIF-1 α, Glut-1, Ki67, P53, and MVD expressions in tumors were downregulated by OA combined with radiation as well as with radiation alone. Additionally, there was a significant positive linear correlation between TMR and HIF-1 α, Glut-1, Ki67, P53, and MVD. Conclusions . These results suggest that OA has a radiosensitizing effect on C6 tumors in terms of tumor volume inhibition, survival extension, and multiple poor prognosis biological markers downregulation. 18 F-FMISO PET/CT can be of value for tumor biology noninvasive capture and radiosensitization response evaluation.